Rationale and design of the INNOVATE Trial: an international cooperative study on surgical versus conservative treatment for odontoid fractures in the elderly - Huybregts, Jeroen GJ (BioMed Central, 2014)
BACKGROUND: Fractures of the odontoid process of the axis are the most common fractures of the geriatric cervical spine. As the population ages, their incidence is expected to increase progressively, as is the number of very old patients (>80 years) with an odontoid fracture. No consensus exists on the optimal treatment (surgical or conservative) and the most relevant outcome parameter (osseous union, fracture stability or clinical outcome). The aim of the INNOVATE (INterNational study on Odontoid frActure Treatment in the Elderly) Trial is to prospectively assess fracture healing and clinical outcome after surgical and conservative treatment for odontoid fractures in the elderly patient, with a specific focus on the very old patient. METHODS/DESIGN: The trial is an observational study in which eleven centres in five European countries are involved. All patients admitted to one of these centres who meet the selection criteria (≥55 years, acute (<two weeks) type II/III odontoid fracture, no rheumatoid arthritis, no ankylosing spondylitis, no previous treatment for odontoid fracture) are asked to participate. The applied treatment is in accordance with usual care and chosen by the treating surgeon and patient. A cohort of 275 patients will be included. Clinical and radiological follow-up moments are scheduled at 6, 12, 26, 52 and 104 weeks, at which both surgeon and patient will complete Case Record Forms (CRFs). The primary outcome will be a combination of fracture healing and clinical outcome at 52 weeks. Osseous union and fracture stability will be assessed with CT-imaging and dynamic X-ray. Clinical outcome will be scored by the Neck Disability Index (NDI) and correlated to the imaging data. Additionally, predefined subgroup analysis will be carried out (i.e. for patient age and osteoporosis) and prognostic factors will be identified. DISCUSSION: Evidence for the optimal treatment for odontoid fractures is lacking. Focusing on both fracture healing and clinical outcome, the results of this study will yield valuable information enabling more rational decision making in the treatment for odontoid fractures in the elderly. TRIAL REGISTRATION: Netherlands Trial Register NTR3630